Respuesta :

Answer:

x = 2.

Step-by-step explanation:

Multiply (2x - 4) by 2 to get (4x - 8). Multiply (2x - 4) by 3 to get (6x - 12). You then get (4x - 8) = (6x - 12). Subtract 4x from both sides of the equation to get -8 = 2x - 12. Add 12 to both sides of the equation to get 4 = 2x. Divide both sides by 2. You then end up with x = 2. Hope this helps!

2(2x-4)=3(2x-4)

Step 1: Distribute 2 to the numbers in the parentheses on the left side. This would be: (2x - 4) only on the left side

(2 × 2x) + (2 × (-4)) = 3 (2x - 4)

4x + ( -8 ) = 3 (2x - 4)

4x -8 = 3 (2x - 4)

Step 2:  Distribute 3 to the numbers in the parentheses on the right side. This would be: (2x - 4) only on the right side

4x -8 = (3 × 2x) + (3 × (-4))

4x -8 = 6x + (-12)

4x -8 = 6x -12

Step 3: Combine like terms

x's go with x's by subtracting 4x to both sides

(4x - 4x) -8 = (6x - 4x) -12

-8 = (6x - 4x) -12

-8 = 2x -12

normal numbers ( -8 and -12) need to be combined. Do this by adding 12 to both sides

(-8 + 12) = 2x + (-12 + 12)

4 = 2x

Step 4: Isolate x by dividing 2 to both sides

[tex]\frac{4}{2} =\frac{2x}{2}[/tex]

2 = x

x = 2

Hope this helped!

ACCESS MORE